An assessment on the effectiveness of the internal audit function at Fabco Pvt Ltd - Dhliwayo, Nyasha (2014)
The purpose of this research was to assess the effectiveness of the internal audit function at Fabco Pvt Lt. The questioning of the necessity of internal audit by the major shareholder and recurrent increased stock write-offs without adequate explanations by management probed the researcher to carry out the study. The study involved internal audit personnel, management and accounts staff. The study sample composed of three internal audit personnel, five managers and four accounts personnel. Research instruments considered for the purposes of this research are questionnaires which had 92% response rate and interviews which yielded 89% response rate. Data accumulated was analysed and presented through graphs, tables and pie charts and rational conclusions were drawn from this. Upon analysis of the accumulated data, the results of the study suggest that the audit policy is not formally documented and adequately disseminated to staff. It was also seen that there is no independent internal audit committee to review the work of internal auditors and that the entity in question does not engage calibre staff. The recommendations forwarded by the researcher are envisaged to lead to effectiveness of the internal audit function at Fabco Pvt Ltd.